2012
DOI: 10.1038/nature11305
|View full text |Cite
|
Sign up to set email alerts
|

Protocadherins mediate dendritic self-avoidance in the mammalian nervous system

Abstract: Dendritic arbors of many neurons are patterned by a process called self-avoidance, in which branches arising from a single neuron repel each other1-7. By minimizing gaps and overlaps within the arbor, self-avoidance facilitates complete coverage of a neuron’s territory by its neurites1-3. Remarkably, some neurons that display self-avoidance interact freely with other neurons of the same subtype, implying that they discriminate self from non-self. Here, we demonstrate roles for the clustered protocadherins (Pcd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

21
503
4
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 426 publications
(529 citation statements)
references
References 53 publications
(102 reference statements)
21
503
4
1
Order By: Relevance
“…The striking findings of Lefebvre et al [13] have supported this view by pinpointing a role for Pcdhs in self-recognition and self-avoidance in mammalian neurons. The authors focused on the Pcdh-γ cluster (Pcdhg), which was previously shown to be important for neuronal survival and synapse formation [14,15].…”
supporting
confidence: 67%
See 1 more Smart Citation
“…The striking findings of Lefebvre et al [13] have supported this view by pinpointing a role for Pcdhs in self-recognition and self-avoidance in mammalian neurons. The authors focused on the Pcdh-γ cluster (Pcdhg), which was previously shown to be important for neuronal survival and synapse formation [14,15].…”
supporting
confidence: 67%
“…The authors focused on the Pcdh-γ cluster (Pcdhg), which was previously shown to be important for neuronal survival and synapse formation [14,15]. Mouse retinal starburst amacrine cells (SACs) express Pcdhg genes and display clear evidence of dendritic self-avoidance [13,14]. Using a pan-retina Cre driver to delete all 22 Pcdhg genes from all retinal cells, the authors observed increased SAC dendritic self-crossings and fasciculation ( Figure 1).…”
mentioning
confidence: 99%
“…This diversity appears to play a fundamental role in neural circuit assembly (22)(23)(24)(25). Understanding the mechanism by which this diversity is generated is, therefore, fundamental to understanding the development and function of the nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed a functional role for clustered Pcdh genes in dendritic development and self-avoidance [22][23][24][25]. Strikingly, a repertoire of heterozygous mutations in chromatid-segregating cohesin (SMC1A, SMC3, RAD21) and cohesin regulators (NIPBL, ESCO2) have been found to cause a class of developmental disorders known as Cornelia de Lange syndrome (CdLS) and Robert syndrome in humans (31).…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that the role of the Pcdhg cluster in neuronal survival is primarily, if not entirely, mediated by one or more of the C-type isoforms, which are phylogenetically divergent among Pcdhs, and exhibit different expression patterns from the alternate isoforms. However, as the full cluster deletion mutants still die as neonates in the absence of apoptosis, the Pcdhg proteins must have an additional independent role that is essential for postnatal development, most likely in neural circuit assembly.Such a role was dramatically revealed in a detailed genetic study, where Pcdhg proteins were shown to mediate neurite self-avoidance in retinal starburst amacrine cells (SACs), as well as in cerebellar Purkinje cells (Lefebvre et al, 2012). Self-avoidance is a fundamental principle in neural circuit assembly, whereby sister axons and dendrites of the same neuron recognize and repel each other, while allowing multiple neurons to share the same receptive or projection field (Kramer and Kuwada, 1983).…”
mentioning
confidence: 99%